Utilização da metodologia ahp para alocação de equipamentos telecomandados em sistemas de distribuição para melhoria da confiabilidade - Daza, Eric Fernando Boeck (2010)
In power utilities the subject reliability is a permanent worry. In this new context, some solutions have been developed and researched to an alternative to improve the performance on service restoration when there are consumers without power supply. Among possible solutions the installation of remotely-controlled switches represents a solution that has been adopted by many companies due its cost benefit. The allocation of these devices is essential to assess the different criterions and characteristics, so the use of multi-criteria decision making to evaluate these characteristics and especially to allow the measurement of expert s opinion in power distribution systems is essential. Therefore, the objective of this work is to propose a new methodology for the allocation of these devices in electric distribution systems based on AHP - Analytic Hierarchy Process decision making for validation of the best locations to install theses device. The contribution and innovation of this work consist in adding to the allocation methodology a validation of expert opinion, discarding those that present a very low consistency and thus making the final answer more exact and in accordance with the proposal, through a variation of the AHP methodology.